Accumulation of Malachite Green and Crystal Violet Dye from Synthetic Effluents Using Single Cell Microalgae Chlamydomonas reinhardtii - Yadav, Sneha; Saravanan, P.; Renganathan, S. (Asian Journal of Chemistry, 2014)
In present investigation, Chlamydomona reinhardtii organism was found as novel microalgae used for the bioaccumulation of dye in short period of time within 48 h. The percentage removal and uptake capacity of malachite green and crystal violet using C. reinhardtii with alive biomass was studied under optimized conditions. The survival of organism was studied using the chlorophyll content of the organism in the presence of dye. The accumulation of malachite green and crystal violet dyes using C. reinhardtii was studied as the function of initial pH (1-10) and the initial dye concentration (10 to 400 mg/L). The optimum pH value for both growth and accumulation of the dye was determined as 7. It was observed that C. reinhardtii was capable of removing crystal violet and malachite green with a maximum specific uptake capacity of 173.24 and 183.68 (mg/g), respectively for a dye concentration of 400 mg/L. Higher percentage removal of dye was found at lower concentrations of dye.